Response Process of Coastal Hypoxia to a Passing Typhoon in the East China Sea - Meng, Qicheng; Zhou, Feng; Ma, Xiao; Xuan, Jiliang; Zhang, Han; Wang, Shuai; Ni, Xiaobo; Zhang, Wenyan; Wang, Bin; Li, Dewang; Tian, Di; Li, Jia; et al. (Frontiers in Marine Science, 2022)
Details of the development of coastal hypoxia in response to the passage of Typhoon Bavi (2020) in the East China Sea were reconstructed by numerical modeling using a three-dimensional coupled physical-biogeochemical model. The model was validated via repeated surveys along a transect across a submerged river valley off the Changjiang Estuary before and after the passage of Typhoon Bavi. Before Bavi’s arrival, survey data indicated that the coastal hypoxia had formed off the Changjiang Estuary. However, the hypoxia was not eliminated but instead migrated and aggravated along the observed transect after the typhoon passage. This phenomenon cannot be attributed to the typhoon-induced mixing. Simulation results reveal that the observed development and spatial migration of hypoxia was mainly controlled by typhoon-induced oceanic advection. Results show that Bavi stimulated a regional quasi-barotropic cyclonic loop circulation and coastal downwelling reversing general summer circulation patterns. The onshore transport of the warmer shelf water and subsequent downwelling resulted in a warming of coastal water. The southward coastal current and downwelling induced by the typhoon also led to a migration of the hypoxic zone. Meanwhile, a massive transport of resuspended planktonic detritus from the steep inner shelf and the shallow Changjiang bank toward the submerged river valley occurred. This study reveals that the typhoon-driven currents can play an important role in the development of hypoxia and redistribution of deposited organic matter in coastal shelf seas, which may have both short-term and long-term effects on the regional marine biogeochemical environment.